Reduction of Heavy Metal Levels (Pb and Fe) in Chemical Laboratory Wastewater by the Coagulation Method using Moringa Seeds Bio-coagulants (Moringa oleifera) - Elia Trisnawati; Neni Damajanti (Research in Chemical Engineering, 2023)
Chemical laboratory wastewater treatment is important because contains hazardous wastewater substance that pollute the environment if not treated properly. Instead of to Chemical Oxygen Demand (COD), Total Suspended Solid (TSS), and Biological Oxygen Demand (BOD) content, chemical laboratory wastewater also contains several types of heavy metals, such as Pb and Fe, which are infectious, pathological, and cytotoxic. One of the effective methods to treat the chemical laboratory wastewater is the coagulation-flocculation method with the addition of moringa seed powder bio-coagulant. The aim of this study was to determine the effect of coagulant dose and and precipitation time in reducing Pb and Fe metal levels in chemical laboratory wastewater. This study used variations in coagulant dose (1500, 2000, 2500, 3000, and 3500 mg/L) and precipitation time (20, 30, 40, 50, and 60 min). The result showed that the initial level of Pb and Fe in wastewater were 0.519 and 7.849 mg/L, respectively. The dose of 3000 mg/L of Moringa seed bio-coagulants showed the best concentration to reduce Pb level to 0.084 mg/L. On the other hand, at 3500 mg/L for reduction of Fe into 5.555 mg/L. The precipitation at 30 min showed the best time for reducing level both of Pb and Fe into 0.065 mg/L and 4.569 mg/L, respectively. However, the final level of Pb and Fe of wastewater after coagulation resulting in the below quality standard under The Minister of Environment Regulation Number 5 of 2014.